Jabatan Gerejawi Dalam Sistem Presbiterial Sinodal di GMIM - Tesalonika Bella Piri; Agnes Relly Poluan; Johanna P. Zetlight (Peneliti.net, 2022)
Ecclesiastical positions in GMIM according to the 2021 GMIM Church Order consist of shamas, elders, religious teachers and pastors. These four ecclesiastical offices each have their own duties and functions. Among the congregations in GMIM, they understand that related to the position or positions of these four ecclesiastical offices, there are lower ones. GMIM adheres to a synodal presbyterian church system of government. And in this synodal presbytery system, these four positions have the same position or position, only different functions. This thought that developed in the congregation resulted in the occurrence of a hierarchy of ecclesiastical positions which had an impact on the continuity and smoothness of the fellowship of the congregations in GMIM. This article will discuss what and how the duties and positions of this ecclesiastical office are.